2002
DOI: 10.1046/j.1365-2036.2002.01377.x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety but not depression determines health care‐seeking behaviour in Chinese patients with dyspepsia and irritable bowel syndrome: a population‐based study

Abstract: SUMMARYAims: To study the prevalence of dyspepsia and irritable bowel syndrome and the effects of co-existing anxiety and depression on health care utilization by a population survey in Chinese. Methods: Ethnic Chinese households were invited to participate in a telephone survey using a validated bowel symptom questionnaire and the hospital anxiety and depression scale. Gastrointestinal symptoms were classified as dyspepsia and irritable bowel syndrome according to the Rome I criteria and gastro-oesophageal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
160
2
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(193 citation statements)
references
References 32 publications
24
160
2
7
Order By: Relevance
“…In a study from urban and rural population of southern Iran, the prevalence of reflux symptoms occurring at least 3 times per week was 15.4% [9] . Hu et al [17] demonstrated that only 4.8% of Chinese population had GERD. On the other hand, Wong et al [18] in a study by telephone contact, reported a prevalence of 29.8%.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from urban and rural population of southern Iran, the prevalence of reflux symptoms occurring at least 3 times per week was 15.4% [9] . Hu et al [17] demonstrated that only 4.8% of Chinese population had GERD. On the other hand, Wong et al [18] in a study by telephone contact, reported a prevalence of 29.8%.…”
Section: Discussionmentioning
confidence: 99%
“…24 Using the Rome I criteria, 14.0% of 1649 subjects from Hong Kong had overlapping FGIDs. 25 In a recent Korean study on patients visiting outpatient gastroenterology clinics, 110 of 632 (17.0%) had IBS-FD overlap using the Rome III criteria. 26 Dyspepsia-IBS overlap has clinical significance as these patients may have different pathophysiological mechanisms than pure syndromes, poorer quality of life, inadequate treatment response and need for combination therapies.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…15,16 Psychological characteristics predict likelihood of GERD symptoms. 4 GERD patients with a high frequency of symptoms and long duration of disease have increased psychological distress.…”
Section: Psychological Comorbidity In Gerdmentioning
confidence: 99%